The effects of shade levels and additional calcium nitrate on the morphology of Cyrtandrabracheia B.L. Burt / Siti Maslizah Abdul Rahman ...[et al.] - Abdul Rahman, Siti Maslizah; Yaacob, Adzmi; Wan Abdul Kadir, Wan Mohammad; Mohammad, Zabedah; Shahid, Mahamud; Sayuti, Zulhazmi (2013)
The effects of different shade levels and additional calcium nitrate [Ca(NO3)2] were tested for morphology of Cyrtandrabracheia. Mature C bracheia plants were collected and the healthy leaves (2nd-3rd leaf from top) were chosen for propagation. After five months (3-4 leaf stage), homogenous new plants were selected as plantlets and grown into 1.5 L pots with peat moss: perlite (50:50) and irrigation was provided three times per day. Black polypropylene net was used to provide 56% shade level (6-9 mol/day) and 86% shade level (2-5mol/day). Standard MARDI hydroponic solution (50 ppm N) was applied at two weeks interval. The plants were subjected to 0, 25, 75 and 100 ppm additional [Ca(NO3)2]. Plants under 86% shade showed an increase green color saturation and silvery proportion. In addition, 86% shade with additional [Ca(NO3)2]. had increased the leaf SPAD value. Higher leaf SPAD value comes with darker leaves, which is a preferred trait for foliage plants. The plants look shiny with the highest silvery variegation. Silvery proportion showed positive correlation with leaf hue angle and leaf SPAD value but negatively correlated with leaf 'L '. The result that silvery variegation of C.bracheiawas pronounced in bright green leaves. Consequently, C.bracheiacan be classified as 'shade' loving plants because it adapts well under 86% shade level and photosynthetically very efficient. Data collection suggested that jive months old C.bracheiacan be used as seedlings under 86% shade level without additional [Ca(NO3)2]. for vigorous growth, produce wider, greener and shiny leaves to meet consumer preference. The result of this study can be used as a guide in the nursery production.